2015
DOI: 10.1371/journal.pone.0137042
|View full text |Cite
|
Sign up to set email alerts
|

Culture at a Higher Temperature Mildly Inhibits Cancer Cell Growth but Enhances Chemotherapeutic Effects by Inhibiting Cell-Cell Collaboration

Abstract: Acute febrile infections have historically been used to treat cancer. To explore the underlying mechanism, we studied chronic effects of fever on cancer cell growth and chemotherapeutic efficacy in cell culture. We found that culturing cancer cells at 39°C mildly inhibited cell growth by arresting the cells at the G1 phase of the cell cycle. When cells were seeded in culture dishes at a lower density, e.g. about 1000–2000 cells per 35-mm dish, the growth inhibition was much greater, manifested as many fewer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The cancer literature reports use of different protocols involving exposure of cell lines to hyperthermia from 1 hour 13 up to 3 days 3 , and some cases up for 2 weeks 14 (in most cases 12–36 h) which makes difficult to draw direct parallels between possible molecular mechanisms underlying the in vitro results and the outcomes of the human hyperthermia clinical studies. The Seahorse extracellular flux analyzer has been reported to produce valuable data measuring cancer metabolism under different experimental conditions including, but not limited to the following: testing effects on novel therapies 15–17 , changes in cancer cell substrate preferences 1820 , effects of gene overexpression or knockdown in cancer cells 2123 , effects of hypoxia 20, 24 and cell environmental factors 2527 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cancer literature reports use of different protocols involving exposure of cell lines to hyperthermia from 1 hour 13 up to 3 days 3 , and some cases up for 2 weeks 14 (in most cases 12–36 h) which makes difficult to draw direct parallels between possible molecular mechanisms underlying the in vitro results and the outcomes of the human hyperthermia clinical studies. The Seahorse extracellular flux analyzer has been reported to produce valuable data measuring cancer metabolism under different experimental conditions including, but not limited to the following: testing effects on novel therapies 15–17 , changes in cancer cell substrate preferences 1820 , effects of gene overexpression or knockdown in cancer cells 2123 , effects of hypoxia 20, 24 and cell environmental factors 2527 .…”
Section: Discussionmentioning
confidence: 99%
“…Most experimental evidence underlying this theory is from in vitro studies in which cell cultures were exposed to prolonged periods (24–72 h) of hyperthermia (defined as exposure to 39° – 42°C). In a recent study, Zhu et al, (2015) reported that various cancer cells maintained at 39°C for 72 h demonstrated mild inhibition of cell growth by arresting the cells at the G1 phase of the cell cycle which also resulted in hyperthermia-enhanced efficacy of several chemotherapeutic agents 3 . In contrast to the in vitro experiments, the clinical in vivo protocols typically utilize only short-term exposure to hyperthermia.…”
Section: Introductionmentioning
confidence: 99%
“…First, cancer cells recruit normal stromal cells to establish cancer niches, as exemplified by tumor angiogenesis 23 . Second, cancer cells collaborate with each other 1 ; 2 ; 34 , which is evident not only in vivo, as in their collective invasion in patients 35 and clonal cooperation in animals 36 ; 37 , but also in vitro as demonstrated by the fact that many cancer cell lines cannot survive in a culture dish when cells are seeded in a very low density 34 ; 38 . On the other hand, there are also many fights among different cell types.…”
Section: Normal Cells and Cancer Cells Fight Against Each Other For Tmentioning
confidence: 99%
“…These molecules are able to seize the available substrate-binding sites and further inhibit substrate binding and reactivity. Meanwhile, tumor cells respond differently from normal cells to temperature changes 8 . Therefore, a universal method to quantitatively describe the kinetic properties of LDH and evaluate the effect of inhibitors and temperature can be beneficial for cancer study.…”
Section: Introductionmentioning
confidence: 99%